2011
DOI: 10.1007/s00125-011-2311-5
|View full text |Cite
|
Sign up to set email alerts
|

Metformin activates AMP-activated protein kinase in primary human hepatocytes by decreasing cellular energy status

Abstract: Aim/hypothesisThe glucose-lowering drug metformin has been shown to activate hepatic AMP-activated protein kinase (AMPK), a master kinase regulating cellular energy homeostasis. However, the underlying mechanisms remain controversial and have never been investigated in primary human hepatocytes.MethodsHepatocytes isolated from rat, mouse and human livers were treated with various concentrations of metformin. Isoform-specific AMPKα abundance and activity, as well as intracellular adenine nucleotide levels and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
191
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(208 citation statements)
references
References 50 publications
7
191
0
4
Order By: Relevance
“…It has been shown that metformin activates AMPK through LKB1 because LKB1 is the up-stream kinase regulating the phosphorylation of the AMPK catalytic α subunit at T172, a crucial phosphorylation site for AMPK activity [26] . Alternatively, it has been proposed that metformin activates AMPK via inhibiting mitochondrial complex 1 and consequently increasing the ADP/ATP ratio, a basic stimulating factor for AMPK activity [27,28] . In this study, we observed that AMPK phosphorylation was apparently inhibited by LPS administration, especially in the liver, a major tissue target for the glucose-lowering effect of metformin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that metformin activates AMPK through LKB1 because LKB1 is the up-stream kinase regulating the phosphorylation of the AMPK catalytic α subunit at T172, a crucial phosphorylation site for AMPK activity [26] . Alternatively, it has been proposed that metformin activates AMPK via inhibiting mitochondrial complex 1 and consequently increasing the ADP/ATP ratio, a basic stimulating factor for AMPK activity [27,28] . In this study, we observed that AMPK phosphorylation was apparently inhibited by LPS administration, especially in the liver, a major tissue target for the glucose-lowering effect of metformin.…”
Section: Discussionmentioning
confidence: 99%
“…The successfully established diabetic KK-Ay mice ( n  = 41) were randomly divided into four groups: vehicle group (saline treatment, n  = 10); SMR-treated groups (50 mg/kg/day, n  = 10; 100 mg/kg/day, n  = 11). As we all known, metformin is a commonly used anti-diabetic drug which has been demonstrated can increasing GLUT4 expression and translocation through activating AMPK pathway [28,29]. So we choose metformin as a positive control drug (200 mg/kg/day, n  = 10).…”
Section: Methodsmentioning
confidence: 99%
“…In mammals, metformin is generally believed to act through the activation of AMPK, one of the main regulators of cellular energy homeostasis (2,(14)(15)(16), but recent research suggests the existence of AMPK-independent mechanisms as well (17,18). More upstream, metformin is thought to activate AMPK through partial inhibition of complex I of the electron transport chain (ETC) and a resultant increase in the AMP/ATP ratio (19)(20)(21), although again, not all data support this theory (16,22).…”
mentioning
confidence: 99%